Optimization of a Two-Species Microbial Consortium for Improved Mcl-PHA Production From Glucose–Xylose Mixtures - Zhu, Yinzhuang; Ai, Mingmei; Jia, Xiaoqiang (Frontiers in Bioengineering and Biotechnology, 2022)
Polyhydroxyalkanoates (PHAs) have attracted much attention as a good substitute for petroleum-based plastics, especially mcl-PHA due to their superior physical and mechanical properties with broader applications. Artificial microbial consortia can solve the problems of low metabolic capacity of single engineered strains and low conversion efficiency of natural consortia while expanding the scope of substrate utilization. Therefore, the use of artificial microbial consortia is considered a promising method for the production of mcl-PHA. In this work, we designed and constructed a microbial consortium composed of engineered Escherichia coli MG1655 and Pseudomonas putida KT2440 based on the “nutrition supply–detoxification” concept, which improved mcl-PHA production from glucose-xylose mixtures. An engineered E. coli that preferentially uses xylose was engineered with an enhanced ability to secrete acetic acid and free fatty acids (FFAs), producing 6.44 g/L acetic acid and 2.51 g/L FFAs with 20 g/L xylose as substrate. The mcl-PHA producing strain of P. putida in the microbial consortium has been engineered to enhance its ability to convert acetic acid and FFAs into mcl-PHA, producing 0.75 g/L mcl-PHA with mixed substrates consisting of glucose, acetic acid, and octanoate, while also reducing the growth inhibition of E. coli by acetic acid. The further developed artificial microbial consortium finally produced 1.32 g/L of mcl-PHA from 20 g/L of a glucose–xylose mixture (1:1) after substrate competition control and process optimization. The substrate utilization and product synthesis functions were successfully divided into the two strains in the constructed artificial microbial consortium, and a mutually beneficial symbiosis of “nutrition supply–detoxification” with a relatively high mcl-PHA titer was achieved, enabling the efficient accumulation of mcl-PHA. The consortium developed in this study is a potential platform for mcl-PHA production from lignocellulosic biomass.